Exploring Political Bias in Captured Media: The Study of Local Press in Lithuania Using Computational Content Analysis Methods - Ramonaitė, Ainė; Vaiginytė, Adelė (Politologija, 2021)
The article presents an exploratory study of regional media content in Lithuania, carried out using computational content analysis methods. The aim of the study is to reveal the effects of media capture on media content. More specifically, it analyses if and how local government’s control over regional mass media leads to media bias. In addition, the research aims to test the methods of automatic content analysis for the texts in Lithuanian language. The article focuses on two local newspapers known for close relationships with local governments – Druskininkai newspaper “Mano Druskininkai” and Širvintos newspaper “Širvintų kraštas”. For comparative purposes, the local newspapers of four additional municipalities (Utena, Šilutė, Birštonas and Biržai) are added to the analysis. The data revealed two different mechanisms for consolidating political power through the politically controlled media: in one newspaper, the dominant technique is the promotion of the mayor as a person, while in the other it is the attack of political opponents.
Keywords: regional media; captured media; media bias; local politics; computational content analysis